THE INFLUENCE OF INCOME ON HOUSEHOLD MOTORCYCLE OWNERSHIP IN BULELENG REGENCY, BALI - Wedagama, D. M. Priyantha (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 17, No. 1, Januari 2013, 2013)
Abstract: This study investigates the influence of income on household motorcycle ownership in Buleleng Regency, Bali using a Multinomial Logit Model. The household income in 2011 is about 15%, 28% and 57% to influence a household owning no, 1 and more than 1 motorcycles respectively. The probability of motorcycle ownership rises substantially by more than 15% for the next 20 years if household income in Buleleng Regency increases. This is particulary applied for the household owning more than 1 motorcycle. In contrast, the probability of a household owning no and 1 motorcycle drops significantly by almost 32% and 14% respectively for the next 20 years if household income in Buleleng Regency increases. A huge number of motorcycles used on the road continuously may lead to serious transport problems for the next few years. This is related to the negative impacts of transport including road accidents and traffic pollution. Improving the existing public transport and introducing a high quality public transport service within and to/from Buleleng Regency is urgently required. The fare of such high quality public transport service however, must be sufficiently low to compete with the cost of riding a motorcycle. In addition, a significant amount of fare subsidy from both local and central government is considerably required.
Keywords: Household Income, Motorcycle Ownership, Multinomial Logit Model.